Snapping Hip Syndrome and Muscle Stiffness - Job, Taylor (My University, 2025)
Muscle stiffness may contribute to tendon stiffness and increase injury risk, specifically in the case of external snapping hip syndrome (ESHS). The objectives of this research are to determine if there is a correlation between iliotibial band (ITB) stiffness and tensor fascia latae (TFL) or gluteus maximus (GM) stiffness, to compare the ITB stiffness between dancers and controls, to compare the stiffness of the ITB in the dominant and non-dominant legs, and to compare the interaction between dance participation and symmetry of ITB stiffness from limb-to-limb. It is hypothesized that a stiffer TFL/GM will be correlated with a stiffer ITB, dancers will have a stiffer ITB than the control group, the dominant legs will have stiffer ITBs, and dancers will have greater differences in ITB stiffness between limbs. Shear wave elastography (SWE) will be used to determine how muscle stiffness correlates with ESHS. Participants were recruited through flyers and a university's science and dance club. There were 13 participants total, 8 dancers and 5 controls, none of them dropped out and no data had to be excluded. Images were taken of participants TFL, GM, and ITB. The data was analyzed by taking the average of the three images at each location and performing linear regressions to determine correlations between ITB and muscle stiffness. A series of independent samples and dependent samples paired t-tests were run to determine if there were any differences between the dancer and control group’s ITB, or between limbs within the dancer and control groups. TFL was found to have no correlation to the ITB while GM had a correlation. ITB stiffness between dancers and controls was not found to be statistically significant but there was a moderate effect size found. Control ITB from dominant to nondominant was found to be statistically significant while dancers were not, suggesting dancers have more limb-to-limb symmetry than controls.
Keywords: Ultrasound, Elastography